Power-Flow Development Based on the Modified Backward-Forward for Voltage Profile Improvement of Distribution System - Suyanto Suyanto; Citra Rahmadhani; Ontoseno Penangsang; Adi Soeprijanto (Institute of Advanced Engineering and Science, 2016)
Unbalanced three-phase radial distribution system has a complex problem in power system. It has many branches and it is sometimes voltage profile’s not stable at every end branches. For improvement of voltage profile, it can be performed by penetrating of a distributed generation models. Information of voltage profile can be gained by study of power flow. The Modified Backward-Forward is one of the most widely used methods of development of power flow and has been extensively used for voltage profile analysis. In this paper, a study of power flow based on the Modified Backward-Forward method was used to capture the complexities of unbalanced three phase radial distribution system in the 20 kV distribution network in North Surabaya city, East Java, Indonesia within considering distributed generation models. In summary, for the informants in this study, the Modified Backward-Forward method has had quickly convergence and it’s just needed 3 to 5 iteration of power flow simulation which’s compared to other power flow development methods. Distributed Generation models in the modified the modified 34 BUS IEEE system and 20 kV distribution network has gained voltage profile value on limited range. One of the more significant findings to emerge from this development is that the Modified Backward-Forward method has average of error voltage about 0.0017 % to 0.1749%.